Modelling Economic High-Frequency Time Series - Stefan Lundbergh; Timo Teräsvirta (Tinbergen Institute, 1999)
In this paper we introduce the STAR-STGARCH model that can characterizenonlinear behaviour both in the conditional mean and the conditionalvariance. A modelling cycle for this family of models, consisting ofspecification, estimation, and evaluation stages is constructed.Misspecification tests for the estimated model are obtained using standardasymptotic distribution theory. We illustrate the actual modelling byapplying the STAR-STGARCH model family to two series of dailyobservations, the Swedish OMX index and the exchange rate JPY-USD.
Keywords: 330; Schätztheorie; Zeitreihenanalyse; Theorie